Analysis of Factors Influencing the “Added Value” in English Academic Quality of Students in Higher Vocational Colleges - Hu, Xiaoli (Journal of Social Science and Humanities, 2025)
This study examines key factors influencing students’ English learning, including student-specific, teaching-related, and school environmental factors, aiming to provide a basis for improving English teaching quality and learning outcomes. Data were collected through literature review, questionnaires, and interviews. Results show that learning motivation, attitude, strategies, and habits are critical intrinsic factors; teachers’ instructional abilities, methods, curriculum design, and textbook selection directly affect learning effectiveness; the school’s English learning atmosphere, resources, and management support systems also have significant impacts. The study recommends that schools enhance guidance on student motivation and strategy training, teachers improve teaching skills and innovate methods, and institutions optimize curriculum and resource management. Future research could further quantify relationships between factors and develop tailored improvements based on regional and institutional contexts.